FIRST RECORD OF THE ASIAN CLAM Corbicula largillierti (PHILIPPI, 1844) IN THE LOWER SÃO FRANCISCO RIVER, NORTHEASTERN BRAZIL (Environmental Smoke, 2023)
The Asian clam of the genus Corbicula is the most successful freshwater invader worldwide. In this research note, the presence of the Corbicula largillierti is recorded for the first time in the Lower São Francisco River. This record is based on the collection of living organisms from the Xingó Hydroelectric Power Plant reservoir. This is the second corbiculid species recorded in the region. Further investigation is required on characteristics such as its distribution, interactions with native and other invasive species, as well as its possible environmental impact.